Differential Effects of Oral and Intravenous Lipid Administration on Key Molecules Related to Energy Homeostasis - Vamvini, Maria T. (J Clin Endocrinol Metab, 2016)
CONTEXT: The spectrum of lipid-induced changes in the secretion of hormones important in energy homeostasis has not yet been fully elucidated. OBJECTIVE: To identify potential incretin-like effects in response to lipid administration, we examined the short-term effect of iv vs oral lipids on key molecules regulating energy homeostasis. DESIGN, INTERVENTION, AND PARTICIPANTS: After a 10-hour overnight fast, 26 subjects were randomized to receive an oral lipid load, a 10% iv lipid emulsion, a 20% iv lipid emulsion, or an iv saline infusion. We obtained blood samples at 30-minute intervals for the first 2 hours and hourly thereafter for a total of 6 hours. MAIN OUTCOME MEASURES: Circulating levels of insulin, glucose, c-peptide, free fatty acids, incretins (glucagon-like peptide-1, gastric inhibitory polypeptide), glucagon, peptide YY, ghrelin, fibroblast growth factor 21, fetuin A, irisin, omentin, and adiponectin were measured. RESULTS: Oral lipid ingestion resulted in higher glucagon-like peptide-1, gastric inhibitory polypeptide, glucagon, and peptide YY levels, compared with the other three groups (incremental area under the curve P = .003, P < .001, P < .001, P < .001, respectively). The 20% lipid emulsion, leading to higher free fatty acid levels, resulted in greater insulin, c-peptide, and fibroblast growth factor 21 responses compared with placebo and the other two groups (incremental area under the curve P = .002, P = .005, P < .001, P < .001, respectively). Omentin, adiponectin, fetuin A, and irisin levels were not affected by either mode of lipid administration. CONCLUSIONS: Metabolic responses to lipids depend on the route of administration. Only iv lipids trigger a dose-dependent fibroblast growth factor 21 secretion, which is nonglucagon mediated. Intravenous lipids also induce hyperinsulinemia without concurrent decreases in glucose, a phenomenon observed in insulin-resistant states. Orally administered lipids mostly affect gastrointestinal tract-secreted molecules important in glucose and energy homeostasis such as glucagon, incretins, and peptide YY.